Virtual Hierapolis - Massimo Limoncelli. (İstanbul)
xi, 231 sayfa
Keywords: “This new volume in the series dedicated to Hierapolis presents the results of an ambitious project concerning the 3D reconstructions of its main monuments and the virtual restoration of the artefacts and pictorial and mosaic decorations, present above all in the houses of the city’s aristocracy. Some of these items have already been described in previous publications, but in this volume, together with hitherto unseen images, they are part of the Virtual Tour of the city, which can also be experienced via on-line and off-line platforms, choosing from three different visitor itineraries. As well as the specific need to study the ancient architecture by means of 3D virtual reconstructions, the creation of the Virtual Tour of Hierapolis provides an answer to the questions posed by the rising number of tourists, which now exceeds two million a year, placing the city, together with Ephesus, among the most popular archaeological sites in Turkey. These reconstructions proved to be highly effective communication tools, enabling the viewing public to understand the appearance of the ancient buildings. Some of these virtual reconstructions were published in 2009 in the leaflet on Virtual Hierapolis, distributed to scholars and visitors. M. Limoncelli was a constant presence in the MAIER in those years, but it was only during his Research Doctorate at the Sacro Cuore Catholic University in Milan, in the years 2013-2016, that his Project was systematically fulfilled“ -- Yayıncı.